Pengendalian Persediaan Bahan Baku Untuk Menunjang Kelancaran Proses Produksi Filter A-5828 (Studi Kasus di Industri Komponen Otomotif) - Hartono, Hartono; Setyo Prabowo, Dwi Ary (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2023)
The production process is a core activity of a company. Production can run smoothly. Agricultural raw materials which are input from the production process are available as needed. The availability of raw materials cannot be separated from planning and control. With the supply of raw materials, the company can meet consumer demand. The raw material inventory system in a company is a part that plays a very important role for a company engaged in manufacturing, in this section it acts as the procurement of raw materials needed by the production process. The high frequency of purchases can result in the large cost of supplies being incurred by the company. This study aims to see the analysis of raw material inventory using the Economic Order Quantity (EOQ) method to increase efficiency in the total cost of inventory. The EOQ method is supported by a Reorder Point (ROP) and Safety Stock. By using EOQ, ROP, and Safety Stock, the company will see the number of orders that must be made, the point of reorder and the amount of safety stock. The total inventory cost was Rp. 3,193,000, 1 roll of Safety Stock and 2 rolls of Reorder Points for 15mm UNP raw materials and Rp. 3,843,600, 2 rolls of Safety Stock and 3 rolls of Reorder Points for 5mm Woll raw materials.Keywords: Production Process, Raw Material, EOQ, Safety Stock, Reorder Point.